Amerika - Michálek, Vladimír 1956-; Duba, Martin; Dejdar, Martin 1965-; Lábus, Jiří 1950-; Sovák, Jiří 1920-2000 (Trade and Leisure Publications, 2003)
This Czech drama is the first film version of Kafka's unfinished novel. The film follows protagonist Karel Rosmann from Europe to America where stays with his Uncle Jacob, an industrialist. Karel has many experiences there that leave him beginning to feel paranoid, especially after he becomes victim to the sexually forward daughter of a business associate of his father. In disgrace he leaves his uncle and takes up with Topic, an alcoholic hobo, and a barmaid, Klara. Topic pushes Karel into a fight and Karel, believing he's killed him goes into hiding where he is protected by Green, a nasty old man, and Mack, a punk. His two protectors are literally the death of him
Based on Franz Kafka's novel Amerika ("je postmodernistickou verzí nedokončeného románu Franze Kafky 'Nezvestný")
Keywords: Film; DVD-Video